Implementasi Moderasi Beragama Melalui Kepramukaan dan Osis Di SMKN 1 Tukak Sadai dan SMKS Yapentob Bangka Selatan - Fauzi (IQRO: Journal of Islamic Education, 2024)
This study aims to analyze the implementation of religious moderation through Scouting activities at SMK Negeri 1 Tukak Sadai and OSIS (student council) activities at SMK Swasta Yapentob Bangka Selatan. Using a qualitative method with interviews, observations, and document analysis, the study found that religious moderation was successfully implemented through programs such as the Moderation Block Camp, community service, communal work at places of worship, and celebrations of religious holidays for Islam, Christianity, Buddhism, and Confucianism. These activities support the development of students' character, fostering virtuous, religious individuals who can maintain harmonious relationships across different religions, ethnicities, and social groups.